A Strategy For Advocacy on Behalf of Women Offenders - Seldin, Stephanie Fleischer (Columbia Journal of Gender and Law, 1995)
Julia’ is a thirty-six-year-old African-American woman incarcerated at the minimum security facility in Lorton, Virginia. She is serving a six-to eighteen-year sentence for writing bad checks. This is her second offense; Julia spent six months in a halfway house for picking up her boyfriend after he robbed a bank. Julia has two boys, ages seven and thirteen. She has not seen them in two months. They are staying with Julia’s mother. Julia has little work experience. Her father raped her when she was in the sixth grade, so Julia left home and worked as a nude dancer to support herself. Julia works in the garment shop, an integrated prison industry. Julia would like to participate in work training, which permits prisoners to work in the community and return to prison in the evening. Julia complains that women are not told that they are eligible for work training; she learned about work training from a male prisoner in the garment shop.